Regulation of cellular senescence in tumor progression and therapeutic targeting: mechanisms and pathways - Liu, Bowei; Peng, Zhigang; Zhang, Hao; Zhang, Nan; Liu, Zaoqu; Xia, Zhiwei; Huang, Shaorong; Luo, Peng; Cheng, Quan (Molecular cancer, 2025)
Cellular senescence, a stable state of cell cycle arrest induced by various stressors or genomic damage, is recognized as a hallmark of cancer. It exerts a context-dependent dual role in cancer initiation and progression, functioning as a tumor suppressor and promoter. The complexity of senescence in cancer arises from its mechanistic diversity, potential reversibility, and heterogeneity. A key mediator of these effects is the senescence-associated secretory phenotype (SASP), a repertoire of bioactive molecules that influence tumor microenvironment (TME) remodeling, modulate cancer cell behavior, and contribute to therapeutic resistance. Given its intricate role in cancer biology, senescence presents both challenges and opportunities for therapeutic intervention. Strategies targeting senescence pathways, including senescence-inducing therapies and senolytic approaches, offer promising avenues for cancer treatment. This review provides a comprehensive analysis of the regulatory mechanisms governing cellular senescence in tumors. We also discuss emerging strategies to modulate senescence, highlighting novel therapeutic opportunities. A deeper understanding of these processes is essential for developing precision therapies and improving clinical outcomes.